Analisis Strategi Pemasaran pada UMKM Depot Glory dengan Menggunakan Metode Analytical Hierarchy Process (AHP) - Jessica Wijaya; Purnomo Purnomo (Teknik Industri Universitas Ma Chung, 2021)
Depot Glory is a food business that faces intense competition in the food industry. To sustain and grow, Depot Glory needs a good marketing strategy. Therefore, to survive, Depot Glory needs to know the internal and external conditions that can influence the marketing strategy. SWOT (strength, weakness, opportunity, threat) analysis is a suitable method to identify these factors. The AHP (analytical hierarchy process) method is used to determine the appropriate strategy that can be implemented by Depot Glory. The research object is the food sold by Depot Glory. The study results provide alternative marketing strategies that Depot Glory can implement. Effective marketing strategies are essential for businesses in the food industry, especially for small businesses like Depot Glory, to compete with others. This study provides insights into how a food business can analyze their internal and external factors and use that analysis to develop a suitable marketing strategy. The SWOT analysis and AHP methods can be helpful tools in identifying the strengths, weaknesses, opportunities, and threats of a business and developing a strategy accordingly.